Neutron powder diffraction studies as a function of temperature of structure II hydrate formed from propane - Rawn, C J; Rondinone, A J; Chakoumakos, B C; Circone, S; Stern, L A; Kirby, S H; Ishii, Y (Canadian journal of physics, 2003)
Neutron powder diffraction data confirm that hydrate samples synthesized with propane crystallize as structure type II hydrate. The structure has been modeled using rigid-body constraints to describe C 3 H 8 molecules located in the eight larger polyhedral cavities of a deuterated host lattice. Data were collected at 12, 40, 100, 130, 160, 190, 220, and 250 K and used to calculate the thermal expansivity from the temperature dependence of the lattice parameters. The data collected allowed for full structural refinement of atomic coordinates and the atomic-displacement parameters. PACS No.: 61.12-q